Combination pelvic rocking exercises with belly dance to reduce labor pain - Ayu Berlita, Cylia Dzikra; Wijayanti, Krisdiana; Sudirman, Sudirman (MEDISAINS, 2021)
Background: Labor pain will get more substantial along with the increase in cervical dilatation and can affect the mother's psychological condition and the welfare of the fetus. Pelvic rocking exercises help reduce pain during labor, but the combined pelvic rocking exercises with belly dance for birth have not been studied. In this study, combining pelvic rocking exercises with belly dance for birth as physical preparation and exercise, especially in the pelvic area, can reduce pain effectively and efficiently so that mothers can give birth vaginally.Purpose: Analyze the effect of intervention combination of pelvic rocking exercises with belly dance for birth to pain intensity of first stage the active phase in mother birth.Methods: This is Quasy experimental research with pretest and posttest with control group design. Respondents were primigravida mothers during the first stage of the active phase. Determination of respondents by accidental sampling obtained the treatment group (n=17) and control group (n=17). The intervention was given for 20 minutes every 1 hour during the first stage of the active phase.Result: The combined intervention of pelvic rocking exercises with belly dance for birth was effective in reducing pain intensity as seen from the average decrease in pain intensity every hour, at the 1st hour of 4.0, the 2nd hour of 3.0, the 3rd hour of 2.7, and the 4th hour of 2.6 (p<0.001)Conclusion: The combination of pelvic rocking exercises with belly dance for birth is effective to pain intensity of the first stage, the active phase in women giving birth.